Personality and coping with a low-control situation: Cross-lagged latent variable analysis - Buško, Vesna (2008)
The study aimed to test the hypothesized nature and directions of personality, appraisals, and coping relationships. The data were collected on a sample of 421 basic military trainees within a follow-up study of coping with low-control stress. Structural equation models used to test hypothesized mediation effects of cognitive appraisals were specified within a 2-wave cross-lagged panel design, with stationarity assumed on theoretical grounds. Partial mediation effects of event stressfulness were confirmed for emotion-focused coping only. The results were compared with those obtained by structural equation analyses done within different methodological framework but tested against the same data sets.
XXIX International Congress of Psychology (20-25.07.2008. ; Berlin, Njemačka)
Projekt MZOS
ENG